Pengembangan Media Pembelajaran Berbasis Augmented Reality (AR) pada Mata Pelajaran IPA Kelas VII - Toha, Defrian Ardianto Putro Fadhlullah; Panggayuh, Vertika (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2024)
The problem in science education at SMPN 1 Karangan is the lack of interactive and technology-based learning media, especially for the complex topics of Earth and the Solar System. This study developed Augmented Reality (AR) based learning media to enhance interactivity and visualization in teaching. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis phase revealed the need for more interactive media. The design was developed using Unity and Canva, with content sourced from reliable science textbooks. Validation results from media and material experts showed scores of 95% and 93%, respectively. The small group trial (10 students) achieved a score of 96%, while the large group trial (30 students) reached 90.6%. The AR media proved effective in improving student understanding and motivation, despite some technical issues. The AR learning media is suitable for use and can enhance understanding of science topics. It is recommended for schools and teachers and should be disseminated through workshops. Further research is needed to test its effectiveness in various contexts and to enrich the content and features of the AR application